Relationship between mitogenic activity of influenza viruses and the receptor-binding specificity of their hemagglutinin molecules. - Anders, E M (1986)
The relationship between the mitogenic activity of influenza type A viruses for murine B lymphocytes and the receptor-binding specificity of their hemagglutinin was examined. Receptor-binding specificity was determined by the ability of the virus to agglutinate erythrocytes that had been sialidase treated and then enzymatically resialylated to contain sialyloligosaccharides with defined sequences. Distinct differences in receptor-binding specificity were observed between strongly and weakly mitogenic viruses of the H3 subtype, with strong mitogenic activity correlating with the ability of the virus to recognize the sequence N-glycolylneuraminic acid alpha 2,6 galactose (NeuGc alpha 2,6Gal). Viruses isolated early in the evolution of the H3 subtype (from 1968 to 1971) are relatively weak mitogens and recognize the sequence N-acetylneuraminic acid alpha 2,6 galactose (NeuAc alpha 2,6Gal) but not NeuGc alpha 2,6Gal. H3 viruses isolated since 1972 are strongly mitogenic, and these viruses recognize both NeuGc alpha 2,6Gal and NeuAc alpha 2,6Gal. The amino acid substitution of Tyr for Thr at residue 155 of HA1 may be critical to this change in receptor-binding specificity and mitogenic activity of the later H3 viruses. Horse serum-resistant variants of H3 viruses, which bind preferentially to the sequence NeuAc alpha 2,3Gal, are poorly mitogenic. Differences were also observed between the receptor-binding specificity of the strongly mitogenic H3 viruses and viruses of the H2 and H6 subtypes, the mitogenic activity of which is limited to strains of mice that express the class II major histocompatibility complex glycoprotein I-E. The results indicate that the receptor-binding specificity of the hemagglutinin plays a critical role in determining the mitogenic activity of influenza viruses.